Drag each equation to show if it could be a correct first step to solving the equation
2 (x + 7) = 36.
_____________________________________
| (2 · x) + (2 · 7) = 36   | 2x + 7 = 36 |
| x + 7 = 18    |   2(x + 7) = 72 |
| 2x + 14 = 36  |  x + 14 = 36 


Yes              No             Not Enough Info


Respuesta :

Answer:

Yes

  • (2 · x) + (2 · 7) = 36
  • x + 7 = 18
  • 2x + 14 = 36

No

  • 2x + 7 = 36
  • 2(x + 7) = 72
  • x + 14 = 36

Step-by-step explanation:

It is appropriate to eliminate parentheses as a first step. This can be done using the distributive property, resulting in either of ...

  • 2x +2·7 = 36
  • 2x +14 = 36 . . . . . 2·7 evaluated mentally

or by dividing the equation by the factor outside parentheses, resulting in ...

  • x + 7 = 18

___

Any of the equations other than these represent violations of the equal sign. Something has been done to one side of the equation without the same thing being done to the other side.

ACCESS MORE